Novel Programmable Solar Based SIMO Converter for SMPS Applications with IOT Infrastructure - Dusarlapudi, Kalyan; Chundu, Sumanjali; Kattupalli Sudhakar; Raju.K, Narasimha (International Journal of Integrated Engineering, 2024)
The technological advancements lead to depend more on electronic goods which consume DC power. The DC appliances need converter circuits that are unique concerning their voltage and current ratings. In this paper, IoT enabled Programmable DC-DC converter is proposed for Solar dependent on DC Loads. The economically viable reconfigurable converter is achieved using a customized IoT board SPELEC. The primary step of the design to feed the SIMO converter from 230-Watt solar panel, the second stage 25 Khz pulses are generated from the SPELEC board to trigger the converter MOSFETs and in the Third stage of design, an MPPT Petrube and Observe (P&O) algorithm is implemented to maintain SIMO converter output Voltage’s constant irrespective of the solar panel voltage fluctuations based on duty change in trigger pulses to the MOSFETs. The design aimed to cater to DC loads of different voltages as 9V 12 V and 24 V act as a solar spike. IoT-enabled features are Solar Panel voltage and Load Currents along with Load isolation using Blynk Mobile operated Relay control. The Sensor data is uploaded for visualization and analysis on Thingspeak Cloud. The recorded voltage is in the range of 0 to 12v and current is 0 to 1.5A and power is from 0 to 20watts. The SPELEC Converter performance is compared with the Arduino-based converter and an improvement in ripples is recorded.